Tinjauan Manajemen Informasi Dan Rekam Medis (MIRM) 11 Dan 14 Standar Nasional Akreditasi Rumah Sakit (SNARS) Di RSU X Tasikmalaya Tahun 2022 - Novi Fidianti; Ida Sugiarti (Akademi Perekam dan Informasi Kesehatan Imelda, 2022)
Hospital accreditation is an acknowledgment of service quality. The results of a preliminary study in the filing room, the storage door was not locked because it was the access door to the medical record room, it was found that medical records were stored in cardboard boxes, storage of files stored in an untidy manner made medical records damaged and folded, and no tracer was available. The purpose of this study was to determine the application of security and confidentiality aspects of medical records according to MIRM 11 and 14. This type of research was qualitative with a phenomenological approach. The research subjects were 4 informants with data collection methods using in-depth interviews, observation, and documentation studies. Data analysis used thematic analysis. The results of the study provided SOP and SK for the prevention of unauthorized use of medical records. Protection from loss by recording in the register book. Protection from damage is to replace the cover, adequate facilities, and there are K3 officers. Protection from access interference is with officers always on guard at the storage room. The protection of the storage room against unauthorized access is that the door is always locked. There are SOP on the confidentiality and privacy of information. Regulations are enforced at the time of release of information and when accessing files. Other compliance officers comply with the time of returning medical records